2016
DOI: 10.1111/1348-0421.12361
|View full text |Cite
|
Sign up to set email alerts
|

HIV RNA and proviral HIV DNA can be detected in semen after 6 months of antiretroviral therapy although HIV RNA is undetectable in blood

Abstract: The risk of sexual transmission of HIV is strongly correlated with amounts of genital HIV RNA. Few studies have reported amounts of HIV RNA and HIV DNA in semen in HIV-infected Chinese patients undergoing antiviral treatment (ART). In this observational study, the amounts of HIV RNA and HIV DNA in semen were assessed after six months of ART in HIV-infected Chinese individuals, when HIV RNA was undetectable in blood . This study included 19 HIV-infected Chinese men undergoing ART for six months. Amounts of HIV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 65 publications
1
9
0
Order By: Relevance
“…Seminal viral shedding of HIV may be associated with co‐infection such as cytomegalovirus , genital inflammations , differences in blood viral loads , ART regimen or duration of ART . In the current study, the undetectable seminal viral load we found after ART may be attributable to the relatively longer duration of ART, which differs from our previous study with only 6 months of ART . Our result is consistent with those of previous studies for 6 months or more than 3 years of ART .…”
Section: Discussionsupporting
confidence: 89%
“…Seminal viral shedding of HIV may be associated with co‐infection such as cytomegalovirus , genital inflammations , differences in blood viral loads , ART regimen or duration of ART . In the current study, the undetectable seminal viral load we found after ART may be attributable to the relatively longer duration of ART, which differs from our previous study with only 6 months of ART . Our result is consistent with those of previous studies for 6 months or more than 3 years of ART .…”
Section: Discussionsupporting
confidence: 89%
“…Recently some studies have shown that it is possible to detect integrated HIV DNA in semen cells in long-term ART experienced men. [29,30] It has been pointed intermittent that seminal shedding of HIV (RNA) in spite of suppression of HIV in blood and persistence of HIV DNA in semen should not be considered to place individuals at greater risk for HIV transmission than previously reported. [26,30] So some of the limitations we used in the early years of our program could be dropped in future.…”
Section: Discussionmentioning
confidence: 99%
“…Paired samples of semen and blood were collected from the seven individuals with early HIV‐1‐infection. The methods for isolating blood plasma, PBMCs, seminal cells and seminal plasma were the same as previously described .…”
Section: Methodsmentioning
confidence: 99%
“…The C2‐V5 region of the HIV‐1 env gene from RNA of blood plasma and seminal plasma and from DNA of PBMCs and seminal cells was analyzed as previously described .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation